Studi Komparasi Kepatuhan Penerapan Protokol Kesehatan Pada Masyarakat Pekerja (Berbasis Zonasi COVID-19) Di Kota Bekasi Tahun 2020 - Siti Rapingah; Safira Andani (Afiat, 2021)
Covid-19 is a disease that attacks the respiratory tract and spreads very quickly, including in Indonesia with a fairly high Case Fatality Rate (CFR) reaching 4.2% and exceeding the CFR in the world, which is 3.3%. COVID-19 zoning). Using the n method of comparative study research with a cross sectional approach, the research site is in RW 11 Jatisari, Bekasi City. The total population is 395 people with a sample of 130 respondents with simple random sampling technique. The analysis used univariate and bivariate using T-test Independent Sample Test with = 5%. The results showed that compliance with the application of protocols based on zoning, namely most of the respondents with good compliance were in the green zone (61.8%) while in the Yellow Zone most of the respondents with poor compliance were (52%). Conclusion In the bivariate analysis, the P value of 0.029 was obtained. Thus, it can be concluded that there is a difference in compliance with the application of health protocols in the green zone, which is better than compliance with health protocols in the yellow zone. Suggestions need to be held education about health protocols, especially PHBS in the community in the yellow zone, so that compliance behavior in the yellow zone can increase.